Analysis of Risk Factors for Skin Disease Symptom at The Waste Disposal Workerin Deli Serdang - Diajeng ayu Sekar zahroh; Putra Apriadi Siregar; Tri Niswati Utami (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Disease risks associated with waste collection and transportation work include skin health problems, increased cases of diarrhea, and skeletal muscle disorders. These circumstances will support the risk of developing skin diseases in waste disposal workers. The purpose;of this study was to determine the relationship between length of service, use of Personal Protective Equipment (PPE), and personal hygiene with symptom of skin diseases among waste transport workers in Deli Serdang. This study is a quantitative study with a cross-sectional design. The sample amounted to 41 people with the sampling technique, namely total sampling. The research instrument was conducted by interview using a questionnaire and conducting field observations to observe waste transportation activities. Data analysis using univariate and bivariate, the statistical test used is the Chi-Square test. The results of research conducted on the relationship between the working period, the use of Personal Protective Equipment (PPE), and personal hygiene in waste transport workers in Deli Serdang, shows that workers who experience skin disease symptom are 41.5%. Based on the results of the chi-square analysis, it was found that there was a signicant relationship between the working period and symptom of skin diseases in waste transport workers where the value (pvalue=0.001), personal hygiene value (p-value=0.012), the use of Personal Protective Equipment (PPE) value (p-value=0.014). Conclusion: Based on the results of the study it can be concluded that there is a relationship between tenure, PPE, personal hygine with complaints of skin diseases in waste carriers. Waste haulers who have less than 5 years of service, compliant use of PPE, and good personal hygine are not at risk for skin disease complaints. Keywords: Personal Hygiene, Personal Protective Equipment (PPE), Work Period